2022
DOI: 10.33988/auvfd.822971
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation capsule therapy via oral route for combatting atopic dermatitis in dogs

Abstract: Given the role of the interaction between gut microbiome with dermatological diseases, namely "gut-skin axis", the present author proved that gut restoration should alleviate canine atopic dermatitis (CAD), which was the purpose of the study. A 4-week, open-label, non-controlled case series involved 8 -owned dogs with CAD which had received no previous treatment. Evaluations included Canine Atopic Dermatitis Extent and Severity Index version 4 (CADESI-04 scores), Visual Analog Scale (VAS) pruritus scores and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
3
14
1
Order By: Relevance
“…That the gut microbiota is an important player in the disease pathogenesis was recently shown by interventional studies using fecal microbial transplantation (FMT) in patients with AD. These studies showed that FMT is safe and efficacious in controlling clinical signs of AD in dogs and humans [ 32 , 33 ]. Therefore, there is a high need for future studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…That the gut microbiota is an important player in the disease pathogenesis was recently shown by interventional studies using fecal microbial transplantation (FMT) in patients with AD. These studies showed that FMT is safe and efficacious in controlling clinical signs of AD in dogs and humans [ 32 , 33 ]. Therefore, there is a high need for future studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, even though it is quite possible to achieve successful FMT treatment in dogs without cleaning their gut microbiota [37,83], it is advisable that veterinary specialists should pretreat recipient dogs with laxatives such as PEG. This increases FMT efficacy by reducing repeated treatment, which is a huge improvement in canine welfare if FMT is delivered through other routes, such as colonoscopy and enema.…”
Section: Future Perspective Of Canine Fmtmentioning
confidence: 99%
“…For example, when 49 CDI patients were treated with encapsulated FMT, the success rate was 88%. However, there is only one report that used commercially available, encapsulated fecal materials used in canine research [83]. Therefore, there may be a prospective study on this matter.…”
Section: Future Perspective Of Canine Fmtmentioning
confidence: 99%
“…Increased serum concentrations of with diarrhoea between 1.5 and 3 months ago may further suggest the possibility that these dogs may develop leaky gut as in humans. We suggest that toxins and allergens entering the organism through the disrupted intestinal barrier and the development of dysbiotic microbiota may have contributed to the development of atopic dermatitis in these dogs (Hua et al, 2016;Pascal et al, 2018;Rostaher et al, 2022;Stewart et al, 2017;K. Ural, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Atopic dermatitis in dogs is thought to be associated with exposure to house dust mite, wheat dust, meadow and grass pollen. However, allergens have been reported to cause seasonal (pollen) or nonseasonal (mites in dust or food) atopic dermatitis (Gedon & Mueller, 2015;Hensel et al, 2015;K. Ural, 2022).…”
Section: Discussionmentioning
confidence: 99%